PPR Control in a Sahelian Setting: What Vaccination Strategy for Mauritania? - ElArbi, Ahmed Salem; Kane, Yaghouba; Metras, Raphaelle; Hammami, Pachka; Ciss, Mamadou; Beye, Assane; Lancelot, Renaud; Diallo, Adama; Apolloni, Andrea (Frontiers in Veterinary Science, 2019)
Peste des Petits Ruminants (PPR) is a viral disease affecting domestic and wild small ruminants. Endemic in large parts of the world, PPR causes severe damages to animal production and household economies. In 2015, FAO and OIE launched a global eradication program (GCSE) based on vaccination campaigns. The success of GCSE shall depend on the implementation of vaccination campaigns, accounting for husbandry practices, mobility and the periodicity of small ruminants’ population renewal. In Mauritania, PPR outbreaks occur annually despite ongoing annual vaccination campaigns since 2008. Here, we developed a mathematical model to assess the impact of four vaccination strategies (including the GSCE one), the importance of their timing of implementation and the usefulness of individual animal identification on the reduction of PPR burden. The model was calibrated on data collected through ad-hoc surveys about demographic dynamics, disease impact and national seroprevalence using Monte Carlo Markov Chain procedure. Numerical simulations were used to estimate the number of averted deaths over the next twelve years. The model results showed that the GSCE strategy prevented the largest number of deaths (9.2 million versus 6.2 for random strategy) and provided one of the highest economic returns among all strategies (Benefit-Cost Ratio around 16 versus 7 for random strategy). According to its current cost, identification would be a viable investment that could reduce the number of vaccine doses to distribute by 20%-60%. Whilst the implementation of the identification system is crucial for PPR control, its success depends also on a coordinated approach at the regional level.